Studies on Mycoflora, Aflatoxigenic Fungi and Aflatoxin in Poultry Feeds. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Poultry feed samples were collected from the Jalgaon district in Maharashtra, and the mycoflora associated with the samples was isolated using agar-plate techniques. Every Aspergillus flavus isolate that was isolated from the samples that were collected was examined for aflatoxigenic potential in SMKY liquid medium. Poultry feeds were used to isolate seventeen distinct fungus. The most prevalent fungus that infest feeds were Aspergillus flavus, A. niger, A. ochraceus, Aspergillus sp., Fusarium sp., and Penicillium sp. Aspergillus flavus dominated all fungi, and 76% of its strains were aflatoxigenic. Crude poultry feed had the highest amount of aflatoxigenic fungus (86.2%). Aflatoxin B1 was estimated in all the samples by extracting the aflatoxin and spotted in an activated thin layer chromatography (TLC) plate with standards and ascertained the concentration by visual comparison method in a UV viewing cabinet. When the natural aflatoxin contamination of poultry feeds was analyzed, 26.67% of the samples had aflatoxin contamination. Maximum concentration of aflatoxin B1 was detected in Local poultry feed (93.67 ppb) followed by Crude poultry feed (92.89 ppb) and Commercial poultry feed (84.38 ppb). poultry feeds contaminated with aflatoxin has poses a potential threat for the life of poultry animals. Hence the regular screening of toxins in every lot of feed prior to feeding the animals or poultry needs to be regularized.